IMPLEMENTASI KEBIJAKAN BANTUAN OPRASIONAL SEKOLAH (BOS) PADA SDN DI KECAMATAN LEMBEAN TIMUR KABUPATEN MINAHASA - Pandoh, Mefry; Rumapea, Patar; Ogotan, Martha (Sam Ratulangi University, 2015)
ABSTRACT: In accordance with the mandate of the Basic Law of the Republic of Indonesia Year 1945 in Article 31 paragraph (1), mandated by the government to provide public access to education in order to develop their potential to the fullest Then the government adopted a program of policy implementation School Operational Assistance (BOS). However, implementation is still encountered some problems and obstacles.The purpose of this study wanted to know how the implementation of school policies Operational assistance (BOS) on SDN in the district of East Lembean Minahasa regency. This study used qualitative methods. Study focused on the type of benefits that will be generated, (who) implementing the program, the resources deployed, as well as power, interests and strategies of the actors involved. Source of data / informants interviewed as many as 15 people consisting of 3 people Principal, 3 BOS Treasurer, 3 school committee, 3 person staff of teachers, and 3 parents and process data collection using interview techniques.The results showed that: the views of the benefits generated is good. But that is not optimal in terms of delay time distribution of aid, the lack of coordination between implementers in this case BOS Management Team School with Parents and less transparency. Recommendations advice to the government in this case BOS Management Team can perform tasks in accordance with the technical guidelines already established, more committed and consistent in carrying out programs or activities, as well as more transparent and involve stakeholders in the implementation of this policy BOS.Keywords: School Operational Assistance Policy Implementation